High-field terahertz pulses generated in an HMQ-TMS organic crystal pumped by an amplified ytterbium laser - Rovere, Andrea; Jeong, Young Gyun; Piccoli, Riccardo; Lee, Seung Heon; Lee, Seung Chul; Kwon, O. Pil; Jazbinsek, Mojca; Morandotti, Roberto; Razzari, Luca (2018 Conference on Lasers and Electro-Optics, CLEO 2018 - Proceedings, 2018)
High-peak-electric-field THz pulses (>200 kV/cm) can be efficiently generated in a recently developed organic crystal pumped by a femtosecond ytterbium laser in a collinear configuration.